2022
DOI: 10.3390/microorganisms10051050
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV-2-Induced Viral Sepsis: The Role of Gut Barrier Dysfunction

Abstract: A considerable proportion of patients with severe COVID-19 meet Sepsis-3 criteria and share common pathophysiological mechanisms of multiorgan injury with bacterial sepsis, in absence of secondary bacterial infections, a process characterized as “viral sepsis”. The intestinal barrier exerts a central role in the pathophysiological sequence of events that lead from SARS-CoV-2 infection to severe systemic complications. Accumulating evidence suggests that SARS-CoV-2 disrupts the integrity of the biological, mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…The latter has been reported to bind to SARS-CoV-2 S protein 57 . LBP is known to increase in the presence of bacterial infections and is a marker of sepsis [58][59][60] COVID-19 patients this LBP increase is caused by dysfunction of the gut-blood barrier that leads to increased microbial translocation 61,62 .…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been reported to bind to SARS-CoV-2 S protein 57 . LBP is known to increase in the presence of bacterial infections and is a marker of sepsis [58][59][60] COVID-19 patients this LBP increase is caused by dysfunction of the gut-blood barrier that leads to increased microbial translocation 61,62 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, three intestinal barrier biomarkers (DAO, D-lactate, and LPS) were used to indicate the different parts of intestinal barrier injury, that DAO reflected the IECs damage [ 16 ], while D-lactate and LPS implied the compromised intestinal barrier integrity [ 17 ]. Under the severe pathophysiology challenges of critical illness, intestinal barrier injury accompanied with compromised intestinal barrier integrity commonly exists in critically ill patients, causing bacterial translocation, systemic inflammatory response, malabsorption, and consequently the poor prognosis [ 7 , 8 , 14 ]. Accordingly, intestinal barrier biomarkers can be used to predict the prognosis of critical illness [ 19 ], and D-lactate has been used in the prognosis of critically ill patients in Qiu’s study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that gut dysbiosis is deeply associated with diabetes [ 27 ], and as the most specific symptom of diabetes, hyperglycemia has been proved to drive intestinal barrier dysfunction, impair intestinal barrier integrity, and cause bacterial translocation [ 12 ]. Nowadays, the cross-talks between diabetes, hyperglycemia, gut dysbiosis, intestinal barrier impairment, bacterial translocation, and systemic inflammatory response are gradually recognized [ 10 , 11 ] and the compromised intestinal barrier integrity and increased bacterial translocation in patients with pre-existing hyperglycemia have been considered to cause worse prognosis in COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations